Research on The General Equilibrium Theory and Reactive Power Pricing in Power Market - Wang, Chengmin; Yi, Tao; Wang, Jie (Elektronika ir Elektrotechnika, 2012)
The general equilibrium model of power market is established considering the power network characteristics by describing the relations between the general equilibrium theory and decision model of power market in this paper. The research on reactive power pricing is made in two-commodity power market, it is indicated that equal price method based on the equilibrium theory of power market is an effective tool and the calculating steps are presented. The case study is made at IEEE-30 system, and it is proved that general equilibrium which is regard as a basic principle in power market pricing is widely existent. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2603